Two years of experience of Y90 microspheres SIRT therapies – A truly multidisciplinary endeavour. (October 2017) - Byrne, Brenda; Rowan, Michael; Lewis, Mandy
Abstract : Selective Internal Radiation Therapy (SIRT) is a targeted treatment for liver tumours that delivers millions of tiny Y90 radioactive beads know as microspheres directly to the liver tumours through the hepatic artery. Y90 is a beta emitter with a half-life of 64 h, maximum energy of 2.27 MeV and produces Bremsstrahlung radiation when interacts with matter. It is a therapy which requires the patient to undergo two angiograms, one for planning and one for the implanting the microspheres, one injection of Tc99m MAA to help plan the therapy and estimate how many of the microspheres could travel to the lungs during the therapy phase, two/three doses of Y90 microspheres delivered to the liver tumours through a catheter, two visits to the nuclear medicine department for imaging, the dispensing of the Y90 microspheres, overnight stay in hospital for the patient and a lot of coordination by a multidisciplinary team of nurses, bed managers, radiographers, medical physicist and consultant radiologists. This presentation will give an overview of our two years of experience of Y90 SIRT therapy which includes the treatment of over 24 patients. The presentation will include details on the risk assessments carried out in advance, the training of staff required, the staff and patient radiation doses, the precautions taken in the interventional laboratory to prevent the contamination of the lab with radioactivity during both angiograms and some of the issues we have discovered with delivering a radionuclide therapy outside of the nuclear medicine department.